A Ni(I)Fe(II) analogue of the Ni-L state of the active site of the [NiFe] hydrogenases - Perotto, Carlo U.; Marshall, George; Jones, Graham J.; Lewis, William; McMaster, Jonathan; Schröder, Martin (Royal Society of Chemistry, 2015)
Ni(L1)Fe(tBuNC)4](PF6)2 is a robust NiIIFeII complex that undergoes a reversible one-electron reduction. Spectroscopic and theoretical studies show that [Ni(L1)Fe(tBuNC)4]+ is an unprecedented NiIFeII species that reproduces the electronic configuration of the Ni-L state of the [NiFe] hydrogenases.